Flow and Immersion in Video Games: The Aftermath of a Conceptual Challenge - Michailidis, Lazaros; Balaguer-Ballester, Emili; He, Xun (Frontiers in Psychology, 2018)
One of the most pleasurable aspects of video games is their ability to induce immersive experiences. However, there appears to be a tentative conceptualization of what an immersive experience is. In this short review, we specifically focus on the terms of flow and immersion, as they are the most widely used and applied definitions in the video game literature, whilst their differences remain disputable. We critically review the concepts separately and proceed with a comparison on their proposed differences. We conclude that immersion and flow do not substantially differ in current studies and that more evidence is needed to justify their separation.